STUDI KERAPATAN DAN PENUTUPAN JENIS LAMUN DI PERAIRAN ENGGANO, BENGKULU - Risnita Tri Utami; Wica Elvina; Yulfiperius Yulfiperius; Ayub Sugara; Ari Anggoro; Teddy Triandiza; La Ode Abdul Fajar Hasidu (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2023)
Seagrass has an important role in coastal ecosystems. Seagrass is a primary producer and constituent of habitats and ecosystems that support life on coral reefs and mangroves or coastal land The distribution of seagrass in Indonesia is quite extensive, covering almost all water areas in Indonesia. Information regarding the distribution of seagrass in the waters of Enggano Island is still limited, so a study is needed to provide information regarding the distribution of seagrass in this area. This study aims to identify the types of seagrass and variations in their density and cover on Enggano Island, Bengkulu. This research was conducted in March 2022 in Kaana Village, Enggano, Bengkulu. Seagrass data collection method using purposive sampling method. Sampling was carried out at four stations, where each station was repeated three times. Seagrass was identified at the research location; its density and closure were calculated. Measurement of water quality is done in situ. The results of this study indicate that three species of seagrass were found, namely Enhalus acoroides, Cymodocea rotundata and Halodule uninervis. However, the types of C. rotundata and H. Uninervis were scattered in all research stations. The highest cover was found at station 1 with 86% cover while the lowest cover was found at station 3 with 16% cover. There are variations in composition and density at each research station, this shows that there is environmental influence and there is not an even distribution of seagrass in the area